HIV vertical transmission preventive measurements used by mothers. - Leal, Aline da Fonseca; Roese, Adriana; de Sousa, Afra Suelene (Investigación y Educación en Enfermería, 2025)
Objective. To analyze HIV vertical transmission preventive measurements used by mothers of HIV positive children who were supported by the Specialized Attention Service (EAS) of the municipality of Pelotas, Rio Grande do sul (Brazil). Methodology. Qualitative research with descriptive and exploratory approach. Data were collected through semi structured interviews applied to five mothers of HIV positive children. The analysis of the information was made through thematic categorization. Results. It was observed that the main factor that hampers HIV vertical transmission preventive measurements was the healthcare staff omission to order the HIV test. Most of the surveyed mothers showed knowledge about the disease and its preventive measurements. Conclusion. There is a need to train health care professionals in the diffusion of preventive measurements to improve prenatal attention.